Effectiveness SIAP on performance civil servants mediated discipline at Bandung environment service - Camilla Sani, Arrumaisha; Sumadhinata, Yelli Eka (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine and analyze the effect of the effectiveness of the application SIAP (Sistem Informasi Absensi Pegawai) on the performance of Civil Servants mediated by variable discipline. This study uses a quantitative approach in the form of descriptive, namely research that emphasizes the analysis of numerical data that is processed using statistical methods. The sample used in this study is using the Slovin formula with a total sample of as many as 55 people. Data processing in the study uses an analysis track or (path analysis). The results of the analysis show that there is no significant effect between the effectiveness of the application attendance electronic (SIAP) on the performance of the employee. The Effectiveness of application attendance electronic (SIAP) shows a positive and significant influence to discipline work. Work discipline can mediate connection Among the effectiveness of using the application (SIAP) with performance employees. This thing shows application attendance through the application (SIAP) does not take effect by direct to performance apparatus at the Bandung City Environment Service, however, with a presented application (SIAP) this makes employees more discipline in access to attendance. Discipline very influences the performance of employees and the organization.